An Intimate Rebuke Female Genital Power in Ritual and Politics in West Africa - Grillo, Laura S. (Religious Cultures of African and African Diaspora People, 2018)
Throughout West African societies, at times of social crises, postmenopausal women - the Mothers - make a ritual appeal to their innate moral authority. The seat of this power is the female genitalia. Wielding branches or pestles, they strip naked and slap their genitals and bare breasts to curse and expel the forces of evil. In An Intimate Rebuke Laura S. Grillo draws on fieldwork in Côte d'Ivoire that spans three decades to illustrate how these rituals of Female Genital Power (FGP) constitute religious and political responses to abuses of power. When deployed in secret FGP operates as spiritual warfare against witchcraft; in public it serves as a political activism. During Côte d'Ivoire's civil wars FGP challenged the immoral forces of both rebels and the state. Grillo shows how the ritual potency of the Mothers' nudity and the conjuration of their sex embodies a moral power that has been foundational to West African civilization.